Biological development and physiological performance of German soccer players from F-youth (6.0-7.9 years) to senior league - Nowacki, P. E.; Keller, H.; Mohammed, H. F.; Nowacki, N. S. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
This study was intended to examine the biological development and the physiological performance of German soccer players from the six age related youth groups ranging from F-Youth (6.0-7.9 y) to A-Youth (16.0-17.9 y) in comparison to players of the Senior League (Senior group 1: 18.0-18.9 y and Senior group 2: >20 y). Subjects were 768 adolescent and 284 adult male soccer players. Biological development of height, weight, vital capacity; graded cycle and treadmill ergometry to exhaustion, performance indices: workload (wattminutes, w/kg bw); VEmax (l BTPS), VO2max (ml/kg); The biological development of body weight, height vital capacity over the years does not differ from age related norms. The physiological fitness profiles demonstrate a high performance level of the tested soccer players at all ages. The physical and cardiorespiratory performance improved continuously with increasing age. Maximal workload increases significantly from 87 to 297 Watt dependent on age. However, a relative workload of 3.5±0.5 w/kg bw which represents a trained physical performance capacity, was reached even by the youngest players. The older players range in the well trained area (4.2±0.6 w/kg kg bw). VEmax increases from 45 to 81 l from F- to C-Youth (12.0-13.9 y) and ranges from 110 to 120 l BTPS (B-Youth and older players). A mean VO2max. of more than 50 ml/kg is reached by all groups. Based on our results, soccer can be recommended as an excellent sports activity for all ages in order to develop and keep a trained physiological performance level.